Shouldering the labor of school desegregation: Stress and health implications for Black families - Linnea Evans; Sienna Ruiz; Akilah Collins-Anderson; Darrell Hudson; Odis Johnson, Jr.; Erin Linnenbringer (SSM: Qualitative Research in Health)
Many U.S. Black students and their families seek quality educational opportunities by enrolling in schools far from their residence via school choice or school desegregation initiatives, a primary impetus to school choice programs. Using data drawn from in-depth interviews and surveys with caregivers of Black student participants (n = 22) who attended one of the few remaining U.S. school desegregation programs, we characterize families' day-to-day experiences with desegregation, including perceived benefits and costs, particularly to health. Study findings highlight added sacrifice and labor relevant to the erosion of health in Black families who seek social mobility through education. Additionally, over half of caregivers participated as children themselves in the St. Louis desegregation program, prompting reflections on their own experiences in relation to their children's experience. From this comparison, we find repetition in the surplus labor exerted by Black families to participate in school desegregation across a generation – evidence we are referring to as the ‘institutionalization of racialized equity labor and intergenerational stress.’ However, the potential health toll was often minimized in participant narratives. In discussing these findings, we consider how minimization is deployed to carry-on through adversity and the implications for education-health research.